Risk-reducing salpingo-oophorectomy for hereditary ovarian cancer - FENG Zheng, WEN Hao (Zhongguo aizheng zazhi, 2022)
Ovarian cancer is one of the most common and lethal diseases among females. Due to the difficulty of surveillance and early detection, most ovarian cancers were diagnosed at advanced stage with poor outcomes. Epidemiological studies indicate that women with deleterious gene mutations have higher susceptibility of ovarian cancer. Thus, it is pivotal to prevent its occurrence. Risk-reducing salpingo-oophorectomy is the most effective method to prevent women at high risk from ovarian cancer. It depends on the standardization of the surgical and pathological procedure. In this article, we aimed to elucidate the current status and controversy of this risk-reducing surgery.